2022
DOI: 10.3390/ijerph20010660
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sports in the Subjective Psychological Well-Being of Hungarian Adult Population in Three Waves of the COVID-19 Pandemic

Abstract: (1) Background: In this study, sport and subjective psychological well-being is investigated in three waves of the COVID-19 pandemic. (2) Methods: We have conducted three different representative sample surveys (n = 3600 altogether) on the Hungarian adult population and investigated the sample’s subjective psychological well-being with the WHO-5 Well-Being Index, as well as changes in their subjective well-being through the different waves of the pandemic. Sporting habits and socio-economic variables were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…In relation to physical activity, the COVID-19 epidemic might also have influenced the attitude of the examined group. Domestic research also supports this regarding the adult Health Problems of Civilization eISSN: 2354-0265, ISSN: 2353-6942 population [8], because it certainly had an impact on the 10-14-year-old age group, since during the pandemic period they mainly relied on primary socialization to achieve a healthy lifestyle.…”
Section: Strengths and Limitationsmentioning
confidence: 82%
“…In relation to physical activity, the COVID-19 epidemic might also have influenced the attitude of the examined group. Domestic research also supports this regarding the adult Health Problems of Civilization eISSN: 2354-0265, ISSN: 2353-6942 population [8], because it certainly had an impact on the 10-14-year-old age group, since during the pandemic period they mainly relied on primary socialization to achieve a healthy lifestyle.…”
Section: Strengths and Limitationsmentioning
confidence: 82%
“…This paper's study interval encompasses the year 2020. Individuals who are infected with COVID-19 during this time may experience a more pronounced drop in subjective wellbeing ( 80 ). On the one hand, this is due to the COVID-19 pandemic, which surely caused a broad sense of anxiety, fear, uncertainty, and insecurity ( 81 , 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the COVID-19 pandemic, the outdoor recreational possibilities tended to be more appreciated: 5 out of 10 respondents said they did not change the frequency of their sports visits, but there were 3 out of 10 did. This latter aspect is crucial because the most recent nationwide survey (LACZKÓ et al, 2023) concluded that those who had been able to increase the timeframe of their sports activities during the pandemic, at the same time, were able to improve their mental and psychological health. Before our survey, it was probable that the characteristics of park use (e.g., frequency of visits, length of training time, number of sports venues used) are related to the distance between the park and the users' residence (H3).…”
Section: Discussionmentioning
confidence: 99%